2008
DOI: 10.1039/b815547j
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol cross-coupling reactions catalyzed by Ru and Ir terpyridine complexes

Abstract: Primary alcohols can be coupled with secondary benzylic alcohols by an air-stable catalytic system involving terpyridine ruthenium or iridium complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 39 publications
0
34
0
2
Order By: Relevance
“…[24] Crabtree et al reported ruthenium-and iridiumcatalyzed cross-coupling reactions between secondary benzylic alcohols and primary alcohols. [25] These results have demonstrated that alcohols can be used as promising green alkylating agents for the a-alkylation of ketones and balkylation of secondary alcohols.R ecently,t ransition-metalcatalyzed a-alkylation of ketones through aB Hp athway has aroused considerable attention as an efficient and atomeconomical method for constructing aC À Cb ond, and it allows convenient introduction of an alkyl group to the a-position of ketones with water formed as the only byproduct.…”
Section: Transition-metal-catalyzed C-alkylation Of Ketones and Seconmentioning
confidence: 96%
See 1 more Smart Citation
“…[24] Crabtree et al reported ruthenium-and iridiumcatalyzed cross-coupling reactions between secondary benzylic alcohols and primary alcohols. [25] These results have demonstrated that alcohols can be used as promising green alkylating agents for the a-alkylation of ketones and balkylation of secondary alcohols.R ecently,t ransition-metalcatalyzed a-alkylation of ketones through aB Hp athway has aroused considerable attention as an efficient and atomeconomical method for constructing aC À Cb ond, and it allows convenient introduction of an alkyl group to the a-position of ketones with water formed as the only byproduct.…”
Section: Transition-metal-catalyzed C-alkylation Of Ketones and Seconmentioning
confidence: 96%
“…[25,44,45] The b-alkylation of secondary alcohols with primary alcohols in the presence of KOHa nd either aruthenium(II)-or iridium(III)/NHC complex catalyst is highly selective in forming the alcohol products 17 [Eq. (7)].…”
Section: B-alkylation Of Secondary Alcoholsmentioning
confidence: 99%
“…Previous studies have also revealed that the ligand environment around ruthenium can play a significant role in determining the catalytic activity of ruthenium complexes. For example, while RuCl 2 (PPh 3 )(2,2 0 :6 0 , 2 00 -terpyridine) effectively catalyzed the coupling reaction between PhCH(OH)Me with PhCH 2 OH, the complexes [(g 6 -cymene)RuCl 2 ] 2 and Cp ⁄ RuCl 2 are essentially inactive for the reaction [12]. These observations promoted us to investigate the catalytic properties of other ruthenium complexes with the intention of finding efficient catalytic systems for b-alkylation of alkyl-substituted secondary alcohols with primary alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of the ruthenium complexes have been tested for the reaction, including RuCl 2 (@CHPh)(PCy 3 ) 2 [20], [(g 6 -cymene)RuCl 2 ] 2 [12,20], RuCl 2 (DMSO) 4 [21], [(g 6 -C 6 H 6 )Ru(o-C 6 H 4 CH 2 NR 2 (NCMe)]PF 6 [22], [(g 6 -cymene)RuCl(pyrimidine-NHC)]PF 6 [13], RuCl 2 (PPh 3 )(2,2 0 :6 0 , 2 00 -terpyridine) [12], RuCl 3 (2,2 0 :6 0 ,2 00 -terpyridine) [12], Cp ⁄ RuCl 2 http://dx.doi.org/10.1016/j.ica.2015.03.023 0020-1693/Ó 2015 Elsevier B.V. All rights reserved. [12], (g 6 -cymene)ruthenium complexes supported by triazolidene [23] and cymene-ruthenium NHC [24], (NHC@imidazolin-2-ylidene, imidazolin-4-ylidene, and pyrazolin-3-ylidene) ligands, [CpRu(CH 3 CN)(PPh 3 ) 2 ]BF 4 [25], CpRuCl(PPh 3 ) 2 [25], CpRuCl(dppm) [25], [TpRu(CH 3 CN)(PPh 3 ) 2 ]BF 4 [25], TpRuCl(PPh 3 ) 2 [25] and cis-[Ru(H 2 O) 2 (6,6'Cl 2 bpy) 2 ](OTf) 2 [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation